2022
DOI: 10.3390/horticulturae8030270
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Effects of CO2 Concentration, Illumination Intensity and Air Speed on the Growth, Gas Exchange and Light Use Efficiency of Lettuce Plants Grown under Artificial Lighting

Abstract: This study investigates and quantifies the integrative effects of CO2 concentration (500, 1000 and 1500 µmol mol−1), illumination intensity (100, 200 and 300 μmol m−2 s−1) and air speed (0.25, 0.50 and 0.75 m s−1) on the growth, gas exchange and light use efficiency of lettuce plants (Lactuca sativa L.) grown under artificial lighting. The results show that lettuce growth and gas exchange are closely related to CO2 concentration and illumination intensity, while air speed enhances CO2 transport during photosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…Moreover, efficiency of combined application of red and blue LED light on photosynthetic rate, leaf transpiration, and stomatal conductance in lettuce plants was recently reported by Ahmed et al. ( 2022 ) which agreed with our results. Blue‐light‐induced stomatal opening is mediated through activation of a plasma membrane (PM) H+ pump, later identified as the PM H+‐ATPase, in guard cells (Assmann et al., 1985 ; Matthews et al., 2020 ; Shimazaki et al., 2007 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, efficiency of combined application of red and blue LED light on photosynthetic rate, leaf transpiration, and stomatal conductance in lettuce plants was recently reported by Ahmed et al. ( 2022 ) which agreed with our results. Blue‐light‐induced stomatal opening is mediated through activation of a plasma membrane (PM) H+ pump, later identified as the PM H+‐ATPase, in guard cells (Assmann et al., 1985 ; Matthews et al., 2020 ; Shimazaki et al., 2007 ).…”
Section: Discussionsupporting
confidence: 93%
“…The low values of photosynthetic characteristics of plants exposed to red LED light were due to deficiency or lack of nitrogen in plant leaves; as a result, the lower the leaf N content, the lower the content of chlorophyll and carotenoid (Kim et al, 2004). Moreover, efficiency of combined application of red and blue LED light on photosynthetic rate, leaf transpiration, and stomatal conductance in lettuce plants was recently reported by Ahmed et al (2022) which agreed with our results. Blue-light-induced stomatal opening is mediated through activation of a plasma membrane (PM) H+ pump, later identified as the PM H+-ATPase, in guard cells (Assmann et al, 1985;Matthews et al, 2020;Shimazaki et al, 2007).…”
Section: Lettuce Varieties Light Spectrumsupporting
confidence: 92%
“…It has been found that the combination of red and blue is used in commercial research and horticulture because these light wavelengths play an important role in photosynthesis and the e ciency of photosynthesis decreases if they are not used 34 . Ahmad et al, 41 reported that the use of red and blue lightemitting diodes increased the photosynthetic rate, transpiration rate, and stomatal conductance in lettuce plants. The researchers found that more than 90% of the blue and red light was absorbed by the plants.…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the reasons why the range of crops grown in CEAL is still quite limited: it is determined primarily by economic efficiency. These are predominantly fast-growing green leafy vegetables, herbs, microgreens, and some fruiting crops [11][12][13][14]. The development and improvement of CEAL technologies requires the expansion of the range of crops and an increase in their adaptation to the controlled environmental conditions.…”
Section: Introductionmentioning
confidence: 99%